Gen Z Interpersonal Communication Patterns in the World of Work in Medan - Jenifer; Putri Ekaresty Haes; Jonathan Jacob Paul Latupeirissa; Putu Suparna (Journal of Communication Studies, 2025)
This research is motivated by the challenges of adapting introverted Generation Z in entering the world of work which demands intense social interaction, team collaboration, and professional adjustment. The purpose of this study is to understand the interpersonal communication dynamics of introverted Generation Z in the transition to the world of work in the city of Medan. This study used a qualitative approach with in-depth interviews with sixteen informants, including introverted individuals aged 18–25 years, two young psychologists, and one job accommodator, and analyzed using the Johari Window theory which divides self-awareness into open areas, blind areas, hidden areas, and unknown areas. The results of the study show that the interpersonal communication of introverted Generation Z develops gradually and reflectively; Their open area expands as confidence and work experience increase, blind areas narrow through feedback receipts, hidden areas decrease as trust in the work environment grows, and unknown areas shrink as their potential is revealed. They develop authentic communication strategies that balance introspection, expression, and social adaptation, without having to turn the personality into extroverted. In conclusion, the survival of introverted Generation Z in the world of work is adaptive and reflective, emphasizing the importance of social experiences, environmental support, and the development of self-awareness to build effective and professional communication.